2, 6-Dihalo-9-selenabicyclo[3.3.1]nonanes and their complexes with selenium dihalides: synthesis and structural characterisation. (17th August 2015) - Potapov, Vladimir A.; Amosova, Svetlana V.; Abramova, Elena V.; Musalov, Maxim V.; Lyssenko, Konstantin A.; Finn, M. G.
Abstract : 2, 6-Dihalo-9-selenabicyclo[3.3.1]nonanes form the 2 : 1 complexes with SeCl2 and SeBr2, which are the first representatives of coordination compounds with the Se⋯Se⋯Se bonds. Abstract : The transannular addition of SeCl2 and SeBr2 to cis, cis -cycloocta-1, 5-diene affords 2, 6-dihalo-9-selenabicyclo[3.3.1]nonanes in high yields. The latter react with SeCl2 and SeBr2 to form the 2 : 1 complexes, which are the first representatives of coordination compounds with the Se⋯Se⋯Se bonds. X-ray crystallographic data of the obtained compounds are discussed. In contrast to 2, 6-dihalo-9-selenabicyclo[3.3.1]nonanes, tetrahydroselenophene does not form complexes with SeCl2 and SeBr2 giving 1, 1-dihalotetrahydroselenophenes.